2018
DOI: 10.1152/jn.00587.2017
|View full text |Cite
|
Sign up to set email alerts
|

The antihelminthic moxidectin enhances tonic GABA currents in rodent hippocampal pyramidal neurons

Abstract: Macrocyclic lactones (MLs) are commonly used treatments for parasitic worm and insect infections in humans, livestock, and companion animals. MLs target the invertebrate glutamate-activated chloride channel that is not present in vertebrates. MLs are not entirely inert in vertebrates, though; they have been reported to have activity in heterologous expression systems consisting of ligand-gated ion channels that are present in the mammalian central nervous system (CNS). However, these compounds are typically no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous investigations have explained that GABA agonists decrease nicotine addiction (Fattore et al, 2009;Varani et al, 2014;Hillmer et al, 2016). Moxidectin has GABA confirm the action and played a character in the decrease of nicotine-induced CPP during this mechanism and it brings about a decrease of nicotine-induced CPP through this mechanism (Spampanato et al, 2018;Menez et al, 2012;Rodrigues-Alves et al, 2008;Huynh et al, 2017). Moxidectin has GABA receptors activity which can contribute to the modulation of nicotine-induced CPP during this mechanism.…”
Section: Discussionmentioning
confidence: 91%
“…Previous investigations have explained that GABA agonists decrease nicotine addiction (Fattore et al, 2009;Varani et al, 2014;Hillmer et al, 2016). Moxidectin has GABA confirm the action and played a character in the decrease of nicotine-induced CPP during this mechanism and it brings about a decrease of nicotine-induced CPP through this mechanism (Spampanato et al, 2018;Menez et al, 2012;Rodrigues-Alves et al, 2008;Huynh et al, 2017). Moxidectin has GABA receptors activity which can contribute to the modulation of nicotine-induced CPP during this mechanism.…”
Section: Discussionmentioning
confidence: 91%
“…A series of recent studies indicated that GABA agonists reduce alcohol dependence (Bechtholt and Cunningham 2005;Banerjee 2014;Martinez et al 2018). It was demonstrated in previous investigations that moxidectin activates GABA receptors (Ménez et al 2012;Huynh et al 2017;Spampanato et al 2018). Moxidectin can contribute to the decrease in ethanol-induced CPP through this mechanism.…”
Section: Discussionmentioning
confidence: 93%
“…The more advantageous central nervous system safety profile of moxidectin is thought to be due to: 1) moxidectin having lower activity on GABA receptors compared to ivermectin which should be an advantage with respect to decreasing contraindications, and 2) differential transport across the blood-brain barrier, with moxidectin being a more limited substrate for P-glycoprotein transporter and lesser dependence on P-glycoprotein for removal from the central nervous system (Huynh et al 2017). Prior research suggests that moxidectin activates P2X4 and GABA receptors (Ménez et al 2012;Franklin et al 2014;Huynh et al 2017;Spampanato et al 2018). P2X4 and GABA receptor systems are observed to be crucial in alcohol addiction (Franklin et al 2014;Huynh et al 2017).…”
Section: Introductionmentioning
confidence: 99%